Implementation of Problem Based Learning Model to Improve Student Learning Outcomes in Mathematics Learning at MIs Nurul Huda Kecipir - Hasan Afandi; Kadmini (Journal of Action Research in Islamic Education, 2025)
This study aims to improve student learning outcomes in Islamic religious education learning by using problem based learning. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were students of elementary madrasahs. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that problem based learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 58.71%, the first cycle 76.39% and in the second cycle it increased to 90.66%. Thus, the use of problem based learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning.